CONSIDERATIONS ON REFUGEE WOMEN IN BRAZIL - Moreira, Elysyana Barros; Gonçalves Júnior, Jucier; Sant´Anna, André Luis; Melo, Antônio Marlos Duarte de; Farias, Athena de Albuquerque; Santaguida, Barbara Maria Moreira Dante; Marinho, Gisanne de Oliveira (Amadeus International Multidisciplinary Journal, 2018)
Throughout history, women have been facing several situations of disregard for basic human rights. In times where entire populations are forced to leave their homes and countries to achieve protection and a minimum condition for survival, as in the case of armed conflicts and political crises, gender relations become even more evident, as women are easy targets of physical and psychological aggression. In these times of greater scarcity of basic resources, they are responsible for caring for the most vulnerable families, the elderly and children. The countries of origin of the refugees - Syria, Iraq, Venezuela, among others – also face problems like inequality and patriarchalism. Refugees are sometimes subjected to sexual violence and, in order to protect themselves, are also forced to marry as children, for instance. These women and girls are not generally seen as human beings but as objects of exchange and weapons of war. It is necessary for international authorities to guarantee protection, shelter and care for refugee women without being required in return for such needed assistance.